Kinetic and structural roles for the surface in guiding SAS-6 self-assembly to direct centriole architecture - Banterle, Niccolò; Nievergelt, Adrian P.; Buhr, Svenja de; Hatzopoulos, Georgios N.; Brillard, Charlène; Andany, Santiago; Hübscher, Tania; Sorgenfrei, Frieda A.; Schwarz, Ulrich S.; Gräter, Frauke; Fantner, Georg E.; Gönczy, Pierre (Nature Communications, 2021)
Discovering mechanisms governing organelle assembly is a fundamental pursuit in biology. The centriole is an evolutionarily conserved organelle with a signature 9-fold symmetrical chiral arrangement of microtubules imparted onto the cilium it templates. The first structure in nascent centrioles is a cartwheel, which comprises stacked 9-fold symmetrical SAS-6 ring polymers emerging orthogonal to a surface surrounding each resident centriole. The mechanisms through which SAS-6 polymerization ensures centriole organelle architecture remain elusive. We deploy photothermally-actuated off-resonance tapping high-speed atomic force microscopy to decipher surface SAS-6 self-assembly mechanisms. We show that the surface shifts the reaction equilibrium by ~104 compared to solution. Moreover, coarse-grained molecular dynamics and atomic force microscopy reveal that the surface converts the inherent helical propensity of SAS-6 polymers into 9-fold rings with residual asymmetry, which may guide ring stacking and impart chiral features to centrioles and cilia. Overall, our work reveals fundamental design principles governing centriole assembly.